2015
DOI: 10.3402/ijch.v74.24298
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in renal replacement therapy in northern Norway 2000–2012

Abstract: ObjectiveDistance from residence location to a centre for renal replacement therapy (RRT) may influence patients’ quality of life and prognosis. Northern Norway constitutes 45% of Norway's landmass, but has less than 10% of the population.MethodsIn this study, we analysed all patients in northern Norway consecutively registered in the Norwegian Renal Registry during 2000–2012. A total of 634 patients (Nordland County 321 patients, Troms County 215 patients and Finnmark County 98 patients) were investigated.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies have shown that the complementary use of telemedicine and in-person consultations is a viable and economic method of medical practice that does not result in a decrease in the quality of care, 12,13 and may improve the quality of care for renal patients. 14 Of the three models described in this study, the block clinic model established in Windsor had the most substantial impact on increasing the number of telemedicine consultations. This clinic model, first described in this study, provides a good template for future nephrology and non-nephrology paediatric block clinics that could be set-up in similar regional sites such as Sudbury or Thunder Bay.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have shown that the complementary use of telemedicine and in-person consultations is a viable and economic method of medical practice that does not result in a decrease in the quality of care, 12,13 and may improve the quality of care for renal patients. 14 Of the three models described in this study, the block clinic model established in Windsor had the most substantial impact on increasing the number of telemedicine consultations. This clinic model, first described in this study, provides a good template for future nephrology and non-nephrology paediatric block clinics that could be set-up in similar regional sites such as Sudbury or Thunder Bay.…”
Section: Discussionmentioning
confidence: 90%